Indirect effects of cigarette butt waste on the dengue vector Aedes aegypti (Diptera: Culicidae) - HamadyDieng, Dieng; Sudha, Rajasaygar; Ahmad, Abu Hassan; Md Rawi, Che Salmah; Hamdan, Ahmad; Tomomitsu, Satho (Elsevier, 2013)
Despite major insecticide-based vector control programs, dengue continues to be a major threat to public health in urban areas. The reasons for this failure include the emergence of insecticide resistance and the narrowing of the spectrum of efficient products. Cigarette butts (CBs), the most commonly discarded piece of waste, also represent a major health hazard to human and animal life. CBs are impregnated with thousands of chemical compounds, many of which are highly toxic and none of which has history of resistance in mosquitoes. This study was performed to examine whether exposure to CB alters various biological parameters of parents and their progeny. We examined whether the mosquito changes its ovipositional behaviors, egg hatching, reproductive capacity, longevity and fecundity in response to CB exposure at three different concentrations. Females tended to prefer microcosms containing CBs for egg deposition than those with water only. There were equivalent rates of eclosion success among larvae from eggs that matured in CB and water environments. We also observed decreased life span among adults that survived CB exposure. Extracts of CB waste have detrimental effects on the fecundity and longevity of its offspring, while being attractive to its gravid females. These results altogether indicate that CB waste indirectly affect key adult life traits of Ae.aegypti and could conceivably be developed as a novel dengue vector control strategy, referring to previously documented direct toxicity on the larval stage. But this will require further research on CB waste effects on non-target organisms including humans.